Nestling sex ratio is associated with both male and female attractiveness in rock sparrows. (13th August 2018) - Cantarero, Alejandro; Pilastro, A.; Griggio, M.
Abstract : According to theory, in species in which male variance in reproductive success exceeds that of the females, sons are more costly to produce; females mated with high quality males or those in better condition should produce more sons. In monogamous species, however, the variance in the reproductive success of the two sexes is often similar and mate choice is often mutual, making predictions regarding sex allocation more difficult. In the rock sparrow Petronia petronia, both males and females have a sexually selected yellow patch on the breast, whose size correlates with individual body condition. We investigated whether the brood sex ratio co‐varies with the size of the yellow patch of the father and the mother in a sample of 173 broods (818 chicks) over 8 breeding seasons. While the size of the yellow patch of the mother and the father did not predict per se a deviation from the expected 1:1 sex ratio, brood sex ratios were predicted by the interaction of male and female yellow patch size. This result is surprising, as the ornament is sexually selected by both males and females as an indicator of quality in both sexes and should therefore be inherited by all offspring irrespective of their sex. It indirectly suggests that other sex‐specific traits associated with patch size (e.g. polygyny in males and fecundity in females) may explain the sex allocation bias observed in rock sparrows. Thus, female individual quality alone, as expressed through the size of the yellow patch, was not associated with the biases in sex ratios reported in this study. Our results rather suggest that sex allocation occurs in response to male attractiveness in interaction with female attractiveness. In other words, females tend to preferentially allocate towards the sex of the parent with more developed ornament within the pair.